Metodologija tematske kartografije nacionalnega atlasa Slovenije - Fridl, Jerneja (Geografija Slovenije, 1999)
The book outlines the scientific achievements of digital cartography developed for the purpose of the National Atlas of Slovenia, published in 1998 with the title Geographical Atlas of Slovenia. Different topics, referring to thematic maps, such as brief description of the history of thematic cartography and various atlases, have been explained. Further on all stages in the working process of digital mapmaking with all the emphasis on appropriate aesthetic solutions in accordance with different content use have been interpreted in detail. Cartographic scientific statements have been emphasised with cases of thematic maps from the Geographical Atlas of Slovenia. The author demonstrates the classical cartographic principles, formed in long lasting development of cartographic profession as well as the newest methodological ascertainments that were applied using the up-to-date digital technology.